2001
DOI: 10.1161/01.atv.21.5.852
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Coronary Calcification in Black and White Young Adults

Abstract: Abstract-Whereas cardiovascular risk factor levels are substantially different in black and white Americans, the relative rates of cardiovascular disease in the 2 groups are not always consistent with these differences. To compare the prevalence of coronary calcification, an indicator of coronary atherosclerosis, in young adult blacks and whites, we performed electron-beam computed tomography of the heart in 443 men and women aged 28 to 40 years recruited from a population-based cohort. The presence of calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
76
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 53 publications
12
76
1
Order By: Relevance
“…2,23,24) Also, an association between MAC and aortic plaque and/or coronary calcification has been shown previously. [25][26][27] Recent data also suggest that cardiovascular calcification is a strong predictor for the presence of CAD and it was suggested that MAC is a manifestation of diffuse atherosclerosis of the vascular system.…”
Section: Discussionmentioning
confidence: 64%
“…2,23,24) Also, an association between MAC and aortic plaque and/or coronary calcification has been shown previously. [25][26][27] Recent data also suggest that cardiovascular calcification is a strong predictor for the presence of CAD and it was suggested that MAC is a manifestation of diffuse atherosclerosis of the vascular system.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, a number of studies have shown that black men had higher IMT of CCA than young, [17] middle age [18] and old white populations [19]. Two population based studies of middle aged men and women [20,21] and one prospective study in post-menopausal women [22] reported similar coronary calcification between black and white men. However, black men had lower coronary calcification in other epidemiological studies [23,24].…”
Section: Discussionmentioning
confidence: 87%
“…(Bild et al 2001;Daviglus et al 2004;Mahoney et al 1998). Here we report cardiovascular risk factors measured prior to and after the menopause as predictors of CaC and AC measured 14.6 to 20.4 years later in 363 women enrolled in the Healthy Women Study.…”
Section: Introductionmentioning
confidence: 99%